EAST JAVA LUDRUK: PRAGMATIC LEARNING PERSPECTIVE ORIENTED CHARACTER EDUCATION - Liesna Andriany; Purwarno Purwarno; Mustofa Mustofa; Saiful Anwar Matondang; Efendi Barus (University of Kuningan, 2023)
The East Java Ludruk show contains many moral values, and one of which contained in the East Java Ludruk text is the value of character education as the character building of the nation. This research aims to reveal moral values as the character building of the nation contained in the East Java Ludruk text by paying attention to linguistic (verbal and nonverbal) and non-linguistic (social, cultural, political, and religious) aspects by applying pragmatic learning based on critical discourse analysis so that character students can easily understand moral values found in the text of the East Jawa Ludruk. In addition, this research also aims to reveal that pragmatic learning in East Java Ludruk texts is also very important and needs to be understood by language teachers because the pragmatics emphasized in this study reveal good speech acts according to pragmatic rules, how to speak according to whom, to whom, where, and how. The results of this study indicate that human values related to the formation of the nation's character are found in the Ludruk text of East Java. In addition, the role of pragmatic learning in East Java's Ludruk text is also very important to facilitate language teachers in expressing good speech acts according to pragmatic learning rules.